2022
DOI: 10.28991/cej-2022-08-10-03
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Effects of Failure Criteria in Assessing Ship Structural Damage Modes

Abstract: The failure to achieve satisfactory results will cause immense losses in major projects. Nevertheless, the modeling limitations and phenomenon assumptions represented by failure criteria can significantly influence the final results—e.g., the damage mode, affecting its quantification—thus representing an interesting topic for technical assessment. This work aims to forecast the effects of several failure criteria on the damage occurring due to structural loading schemes, such as compression, torsion, and tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Additionally, the CEV value of 0.36% is significantly below the standard limit of 0.50%, indicating that the steel's chemical composition should not pose any welding issues. One possible cause of material failure is the application of an external load that exceeds the strength of the material [22][23][24]. This failure can compromise the integrity and performance of engineering components or structures [25][26][27][28].…”
Section: Welding Failurementioning
confidence: 99%
“…Additionally, the CEV value of 0.36% is significantly below the standard limit of 0.50%, indicating that the steel's chemical composition should not pose any welding issues. One possible cause of material failure is the application of an external load that exceeds the strength of the material [22][23][24]. This failure can compromise the integrity and performance of engineering components or structures [25][26][27][28].…”
Section: Welding Failurementioning
confidence: 99%
“…For instance, Kumar et al [5] have demonstrated that the type of stiffener employed plays a crucial role in determining the force-displacement during ship-to-ship collisions. Furthermore, assessing model ship crashworthiness through finite element analysis necessitates the consideration of failure criteria, as highlighted by previous studies [6][7]. Prabowo et al [8] work has shed light on the influence of the collision angle on model deformation.…”
Section: Introductionmentioning
confidence: 99%